2019
DOI: 10.1016/j.bandl.2019.104662
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates and functional connectivity of lexical tone processing in reading

Abstract: Lexical tone processing in speech is mediated by bilateral superior temporal and inferior prefrontal regions, but little is known concerning the neural circuitries of lexical tone phonology in reading. Using fMRI, we examined the neural systems for lexical tone in visual Chinese word recognition. We found that the extraction of lexical tone phonology in print was subserved by bilateral fronto-parietal regions. Seedto-voxel analyses showed that functionally connected cortical regions involved right inferior fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The recruitment of the right homotopic language regions has been well studied. In healthy (right-handed) subjects, right hemisphere language homologues, mainly the right IFG and the temporal lobe, participate in semantic, phonological, and syntactic processing (Tan et al., 2005; Vigneau et al., 2006; Kwok et al., 2019). For patients with left hemisphere damage, language-related structural and functional alterations have been frequently observed in the right hemisphere language homologues (Saur et al., 2008; Turkeltaub et al., 2012; Winhuisen et al., 2007; Xing et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of the right homotopic language regions has been well studied. In healthy (right-handed) subjects, right hemisphere language homologues, mainly the right IFG and the temporal lobe, participate in semantic, phonological, and syntactic processing (Tan et al., 2005; Vigneau et al., 2006; Kwok et al., 2019). For patients with left hemisphere damage, language-related structural and functional alterations have been frequently observed in the right hemisphere language homologues (Saur et al., 2008; Turkeltaub et al., 2012; Winhuisen et al., 2007; Xing et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Tonal languages, in which pitch variation is used to differentiate grammatical or semantic information at the lexical level, have been intensively investigated around two competing hypotheses (Tan & Li, ; Wang, Behne, Jongman, & Sereno, ). The neural characterization of speech perception in tonal languages is accordingly dichotomized into a domain‐specific model (i.e., a functional hypothesis) and a cue‐specific model (i.e., an acoustic hypothesis) (Kwok, Matthews, Yakpo, & Tan, ; Zatorre & Gandour, ). The functional hypothesis assumes that brain activity is lateralized to the left hemisphere (LH) when pitch variance denotes semantic meaning, otherwise to right hemisphere (RH).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our interpretation of the results with caution was that writing-based learning seemed to increase the sensitivity of left MFG to print-to-sound matching, rather than orthographic processing per se Multiple roles have been proposed for MFG in logographic reading, such as visuospatial analysis ( L. Liu et al, 2009 ; C.Y. Wu et al, 2012 ), orthography-semantics association ( Siok et al, 2004 ; J. Wu et al, 2015 ), representing addressed phonology of Chinese words ( Tan et al, 2005a ; Booth et al, 2006 ; Kwok et al, 2019 ; A. Li et al, 2022 ), or encoding writing gestures ( Nakamura et al, 2012 ). The present results showed that a sign of learning effect of the left MFG was observed during orthographic-to-phonological mapping process but not passive reading, which was consistent with insights from a previous meta-analysis that the activity in MFG is task dependent ( Zhao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 91%